Gender and Transport : A Rationale for Action - Bamberger, Michael; Lebo, Jerry; Gwilliam, Kenneth; Gannon, Colin (World Bank, Washington, DC, 2012)
Transport can make a big difference in increasing women's productivity and promoting social equity. Yet, little attention appears to have been paid to women's needs in transport projects. How best can transport policies and projects identify and respond to the needs of women? Making transport policy more responsive to the needs of women requires developing a structured approach to understand their needs, identifying instruments to address those needs, analyzing the costs and benefits of those instruments, and establishing an appropriate policy framework. Moreover, cross-sectoral impacts of transport improvements can serve as a basis for raising gender issues. A first step will be to ensure that at each stage of the planning process, attention is paid to involving women in the planning and implementation of projects that affect them.